PARTICULARIZATION IN INSIDIOUS 4: THE LAST KEY MOVIE (INDONESIAN SUBTITLE) - Lilik Istiqomah; Nurwidayati Nurwidayati; Atatin Atiqotul (UIN Alauddin Makassar, 2019)
This research attempts to find out the translation technique used in Indonesian subtitle, especially for the particularization of “Insidious 4: The Last Key”. This study used descriptive qualitative approach with document analysis since the data consists largely of words. The data source of this study is “Insidious 4: The Last Key” movie. The data are the subtitle of “Insidious 4: The Last Key” movie containing compound- complex sentences taken from www.subscene.com. The finding revealed that they are 53 utterences translated using particularization technique which are divided into 3, they are : (1) Particularization in Word; (2) Particularization in Phrase; and (3) Particularization in Sentence. Particularization in Phrase is divided into 4, that are: (1) Noun Phrase; (2) Verbial Phrase; (3) Prepositional Phrase; and (4) Adverbial Phrase. Keywords: Translation technique, Particularization, SubtitleABSTRAKPenelitian ini bertujuan untuk mengetahui teknik penerjemahan yang digunakan dalam subtitle film berbahasa Indonesia, terutama untuk partikularisasi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan analisis dokumen karena data sebagian besar terdiri dari kata-kata. Data adalah subtitle dari film Insidious 4: The Last Key yang berisi kalimat majemuk yang diambil dari www.subscene.com. Temuan ini mengungkapkan bahwa ada 53 ucapan yang diterjemahkan menggunakan teknik partikularisasi yang dibagi menjadi 3, yaitu: (1) Partikulatisasi dalam kata; (2) Partikulasi dalam Frasa; dan (3) Partikulasi dalam Kalimat. Partikulasi dalam Frasa dibagi menjadi 4, yaitu: (1) Frasa Kata benda; (2) Frasa Verbial; (3) Frasa Preposisi; dan (4) Frasa Adverbia.Kata kunci: Teknik penerjemahan, Partikularisasi, Subtitle